Single-dose immunogenicity and protective efficacy of simian adenoviral vectors against Plasmodium berghei. - Reyes-Sandoval, A; Sridhar, S; Berthoud, T; Moore, A; Harty, J; Gilbert, S; Gao, G; Ertl, H; Wilson, J; Hill, A (2008)
Simian adenoviral vectors (SAd) offer an attractive alternative to standard human adenovirus serotype 5 (AdH5) subunit vaccination, due to pre-existing immunity affecting vaccine performance. We have used a mouse model of liver-stage malaria to test the efficiency of three chimpanzee-origin adenoviral vectors, AdC6, AdC7 and AdC9 containing ME.TRAP as an insert. AdC7 and AdC9 elicited strong immunogenicity ( approximately 20% of CD8(+) T cells in spleen), equivalent to or outperforming AdH5 and inducing sterile protection in 92% (C9), 83% (H5 and C7) and 67% (C6) of the mice, providing the first evidence of single-dose protection to Plasmodium berghei. Protection was afforded by the SAd despite high levels of pre-existing immunity to AdH5. Phenotypic analysis showed that all adenoviral vectors (Ad) elicited CD8(+) T cell responses with an effector memory T cell (T(EM)) phenotype. By contrast, vaccination with poxviral vectors did not confer protection to P. berghei and induced a predominantly CD8(+) central memory T cell (T(CM)) response. Multifunctional CD8(+) T cell responses (co-expressing IFN-gamma, TNF-alpha and IL-2) were also induced by the Ad in higher percentages than the poxviral vectors. Our data suggest that T(EM) cells are important as a first line of defense against fast-replicating pathogens such as murine Plasmodium and demonstrate the potential of replication-defective SAd as future malaria vaccines for humans.